ANALISIS FLUKTUASI HARGA DAN SALURAN PEMASARAN BAWANG MERAH (ALIUM CEVA L) DI KOTA BENGKULU - Nelma Apriyani; Evi Andriani; Rika Dwi Yulihartika (Universitas Muhammadiyah Purwokerto, 2021)
Price fluctuations are the rise and fall of prices, while the marketing channel is the track of the distribution of goods from producers to final consumers. The purpose of this study was to determine the price fluctuations and marketing channels of shallots to shallot traders in the city of Bengkulu. The research method used to determine the price fluctuations of shallots is descriptive method to explain the development of shallot prices presented in the graph. To analyze the marketing channels of shallots, it is described descriptively with a tracing method from wholesaler level to retailer level. The samples of this study were wholesalers and retailers of shallots in the Panorama market and the Sunday market of Bengkulu City with a total sample of 30 traders. The highest price fluctuation in July 2020 reached Rp. 54,500/kg while the lowest price in October 2019 was Rp. 16,900/kg. The shallot marketing channel in Bengkulu City has two channels; the first, wholesalers to consumer scatter traders. Second, wholesalers to wholesalers to retailers to consumers. With a marketing margin of rp. 11,807/kg (48.65%) for retailers and rp. 4.750/kg (20%) for wholesalers. The dominant market share is Toko Ipung with a percentage of 60.89%. With farmer share received by producers 65.69%.